Rob Potential in the Coastal City of Kupang, East Nusa Tenggara (NTT) - Suprabadevi Ayumayasari Saraswati; Lumban Nauli Lumban Toruan; Yulianto Suteja; Dadang Karmen; Putu Eddy Purna Wijaya (Journal of Aquaculture and Fish Health, 2021)
Coastal areas are dynamic and vulnerable to environmental changes, both due to natural processes and human activities, the coastal waters in Kupang City are strategic in supporting the development of the economic sector. Coastal areas have unique characteristics, both in terms of bio-geophysics and social, economic and cultural aspects. Some have a high level of vulnerability to global warming. The high value of vulnerability is inseparable from the geomorphological conditions of Kupang City in the form of sandy beaches and coastal erosion. This condition caused Kupang City to become one of the areas affected by tidal flooding. This research is a preliminary study which aims to determine the potential for rob in the coastal city of East Nusa Tenggara that occurred in February 2014. The impact of the tidal floods submerged residents' houses above the knees of adults as high as 70 cm.. The results of this study were to determine the potential for tidal reoccurrence in the city of Kupang, NTT based on tidal forecasting data. Based on the results of the analysis using the Admiralty method, it was found that the Formzhal (F) value for the coast of Kupang City was 25.82, the position of the lowest water level at Oesapa 2 Beach was 206.9 cm, while the sea level elevation position reached the highest peak on Kelapa Lima 2 Beach, namely 478, 5 cm. The value of the harmonic analysis results from the coastal area of Kupang City has HHWL (Highest High Water Level) which is 340.09 cm, the MSL (Mean Sea Level) value is 212.07 cm, and LLWL (Lowest Low Water Level) is 73.36 cm based on these results. The Kupang coast has the potential for tidal flooding.